Der richtige Ansprechpartner im dynamischen Interaktionsnetzwerk - Trier, Matthias; Müller, Matthias; Bobrik, Annette (HMD Praxis der Wirtschaftsinformatik)

MEDIA ENGINEERING WITH A CONTENT HUB SYSTEM. GENERIC CONTENT TRANSFORMATION FOR MOBILE MEDIA - Herzog, Michael; Trier, Matthias (International Journal of Computing)
A primary problem in multimedia content production is the plethora of formats and the resulting multiple point-to-point transformation processes in different content formatting specifications. However, these content transformation processes can be conceptually broken down into a limited set of abstract principles. This allows a unified approach that theoretically enables the transformation of any given input channel into any desired output. Based on this principle, the present article introduces the concept of Generic Content Transformation and the related project MOCCA, which develops the corresponding software implementation of generic content transformation for a variety of input and output channels. To balance technical similarities with specific properties of different media channels, we suggest a combination of an XML-based structure (MocML) and a high level authoring environment. Generic Content Transformation further allows for novel means of accessing assets via compound search algorithms. In the second part we summarize and discuss current results and experiences in three scenarios of media production, including mobile media.
Keywords: Multimedia Authoring; Mobile Content; Cross Media Production; Content Engineering; Media Retrieval

Business Intelligence 2.0 - Behrendt, Sebastian; Richter, Alexander; Schäfer, Sebastian; Trier, Matthias (Vernetzte Organisation)

Towards a Conceptualization of Online Community Health - Wagner, David; Richter, Alexander; Trier, Matthias; Wagner, Heinz-Theo (Proceedings of the 35th International Conference on Information Systems. ICIS 2014)
Along with the increasing popularity of social media and online communities in many business settings, the notion of online community health has become a common means by which community managers judge the condition or state of their communities. It has also been introduced to the literature, yet the concept remains underspecified and fragmented. In this paper, we work toward a construct conceptualization of online community health. Through a review of extant literature and dialogue with specialists in the field, we develop a multi-dimensional construct of online community health, consisting of seven elements. In writing this paper, we attempt to foster theory development around new organizational forms by advancing a new and important construct. The paper further provides guidance to the managers of social media and online communities by taking a systematic look at the well-being of their communities.
Keywords: Social media; Online communities; Online community success; Online community health; Construct conceptualization

BlogForever: From web archiving to blog archiving - Kalb, Hendrik; Lazaridou, Paraskevi; Banos, Vangelis; Kasioumis, Nikos; Trier, Matthias (INFORMATIK 2013 – Informatik angepasst an Mensch, Organisation und Umwelt)

Establishing interoperability of a blog archive through linked open data - Kalb, Hendrik; Lazaridou, Paraskevi; Trier, Matthias (INFORMATIK 2013 – Informatik angepasst an Mensch, Organisation und Umwelt)

Influence and Dissemination Of Sentiments in Social Network Communication Patterns - Hillmann, Robert; Trier, Matthias (ECIS 2013 Proceedings)
Previous research suggests the existence of sentiments in online social networks. In comparison to real life human interaction, in which sentiments have been shown to have an influence on human behaviour, it is not yet completely understood which mechanisms explain how sentiments influence users in online environments. We develop a theoretical framework that tries to bridge the gap between social influence theories that focus on offline interactions on one hand and online interaction in social networks on the other hand. We then test our hypothesis about the influence and dissemination of sentiments in a quantitative analysis that is based on retrieved textual messages of communication patterns in over 12000 online social networks. Our empirical results suggest a general influence of sentiments on node communication patterns that is evidenced by increased occurrences of subsequent messages that express the same sentiment polarization. We interpret these findings and suggest future research to advance our currently limited theories that assume perceived and generalized social influence to path-dependent social influence models that consider actual behaviour.
Keywords: Social Network Analysis; Sentiment Analysis; Communication Patterns

Interoperability of Web Archives and Digital Libraries: A Delphi Study - Kalb, Hendrik; Lazaridou, Paraskevi; Pinsent, Edward; Trier, Matthias (Proceedings of the 10th International Conference on Preservation of Digital Objects)
The interoperability of web archives and digital libraries is crucial to avoid silos of preserved data and content. While various researches focus on specfic facets of the challenge to interoperate, there is a lack of empirical work about the overall situation of actual challenges. We conduct a Delphi study to survey and reveal the insights of experts in the field. Results of our study are presented in this paper to enhance further research and development efforts for interoperability.
Keywords: Interoperability; Web Archives; Digital Libraries; Delphi Study

Numerical Representations and User Behaviour in Social Networking Sites: Towards a Multi- Theoretical Research Framework - Sjöklint, Mimmi; Constantiou, Ioanna; Trier, Matthias (ECIS 2013 Proceedings)
The new technological enhancements and the accessibility to varieties of online applications, enable users to collect personal data and perform self-evaluation through test, comparison and experimentation. The sparked interest in numbers and numbers as self-representative visualisations is prominent in social networking sites, which are the empirical setting for the present study. This paper sets out to establish a multi-theoretical framework which enables the investigation of emerging phenomena of the role of numbers in social networking sites. The proposed framework rests on three theoretical pillars: self-determination theory, heuristic decision making and behavioural economics. A discussion departs from these convictions to investigate user reactions and behaviour when faced with numerical representations in the SNS.
Keywords: User Behaviour; Social Networking Sites; Numerical Representations; Multi-Theoretical Framework; Quantified Self; Pointification

"I Can Simply…"? Theorizing Simplicity as a Design Principle and Usage Factor - Trier, Matthias; Richter, Alexander
The usage of social software to support collaboration and knowledge management in corporate intranets is a pervasive topic in practice and research. However, there remain many open research questions concerning its socio-technical system design. To address this gap and to contribute to a deeper understanding of the role and success of corporate social software, we first identify and conceptualize simplicity as an influential design principle and usage factor. We propose a theoretical framework that helps us to empirically study the role of simplicity based on six case vignettes of corporate social software implementation and use. From the theoretical basis and the empirical analysis we develop a series of theoretical propositions and discuss implications for IS design and adoption.

Sympathy or strategy: social capital drivers for collaborative contributions to the IS community - Trier, Matthias; Molka-Danielsen, Judith (European Journal of Information Systems)

Blogs as Objects of Preservation: Advancing the Discussion on Significant Properties - Stepanyan, Karen; Gkotsis, George; Kalb, Hendrik; Kim, Yunhyong; Cristea, Alexandra I.; Joy, Mike; Trier, Matthias; Ross, Seamus (iPress 2012)
challenge for the digital preservation community. While the methodological frameworks for selecting these properties provide a good foundation, a continued discussion is necessary for further clarifying and improving the available methods. This paper advances earlier work by building on the existing InSPECT framework and improving its capabilities of working with complex/compound objects like blogs. The modifications enable a more thorough analysis of object structures, accentuate the differences and similarities between the framework’s two streams of analysis (i.e. Object and Stakeholder analysis) and, subsequently, improve the final reformulation of the properties. To demonstrate the applicability of the modified framework, thepaper presents a use case of a blog preservation initiative that is informed by stakeholder interviews and evaluation of structural and technological foundations of blogs. It concludes by discussing the limitations of the approach and suggesting directions for future research.
Keywords: Blogs; Weblogs; Digital Preservation; Significant Properties

Sentiment Polarization and Balance among Users in Online Social Networks - Hillmann, Robert; Trier, Matthias (AMCIS 2012 Proceedings)
Communication within online social network applications enables users to express and share sentiments electronically. Existing studies examined the existence or distribution of sentiments in online communication at a general level or in small-observed groups. Our paper extends this research by analyzing sentiment exchange within social networks from an ego-network perspective. We draw from research on social influence and social attachment to develop theories of node polarization, balance effects and sentiment mirroring within communication dyads. Our empirical analysis covers a multitude of social networks in which the sentiment valence of all messages was determined. Subsequently we studied ego-networks of focal actors (ego) and their immediate contacts. Results support our theories and indicate that actors develop polarized sentiments towards individual peers but keep sentiment in balance on the ego-network level. Further, pairs of nodes tend to establish similar attitudes towards each other leading to stable and polarized positive or negative relationships
Keywords: Social Network Analysis; Ego-Network Analysis; Node Polarization; Sentiment Dissemination

The Blogosphere as Oeuvre: Individual and Collective Influence on Bloggers - Kalb, Hendrik; Trier, Matthias (ECIS 2012 Proceedings)
Blogging has often been described as writing an online diary but, nowadays, it is more diverse and a considerable amount of blogs forms a common interconnected resource – the blogosphere – with comprehensive societal impact. While various studies have inquired social-psychological influenceson the intention to contribute to an individual blog, the perceptions related to creating such a common valuable good have not yet been focussed. Therefore, we introduce a new construct – the oeuvre of blogging – to better account for the notion of the blogosphere as a collective outcome. Furthermore, we propose a research model to inquire the influence of individual and collective beliefs on the oeuvre in comparison to short-term blogging activity. We conducted an online survey with 509 international distributed bloggers to test our model. The results of our study provide support for the importance of an oeuvre construct to explain influences on bloggers and blogging
Keywords: Blog; Blogosphere; Collective benefit; PLS; Knowledge sharing

Dissemination Patterns and Associated Network Effects of Sentiments in Social Networks - Hillmann, Robert; Trier, Matthias (Proceedings of the 2012 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining)
Communication in online social networks has been analyzed for some time regarding the expression of sentiments. So far, very little is known about the relationship between sentiments and network emergence, dissemination patternsand possible differences between positive and negative sentiments. The dissemination patterns analyzed in this study consist of network motifs based on triples of actors and the ties among them. These motifs are associated with common social network effects to derive meaningful insights about dissemination activities. The data basis includes several thousand social networks with textual messages classified according to embedded positive and negative sentiments. Based on this data, sub-networks are extracted and analyzed with a dynamic network motif analysis to determine dissemination patterns and associated network effects. Results indicate that the emergence of digital social networks exhibits a strong tendency towards reciprocity, followed by the dominance ofhierarchy as an intermediate step leading to social clustering with hubs and transitivity effects for both positive and negative sentiments to the same extend. Sentiments embedded in exchanged textual messages do only play a secondary role in network emergence and do not express differences regarding the emergence of network patterns.
Keywords: Social Network Analysis; Dynamic Network Motif Analysis; Sentiment Dissemination; Networking Effects; Triads

CYBEREMOTIONS – Collective Emotions in Cyberspace - Ahn, Junghyun; Borowiec, Anna; Buckley, Kevan; Cai, Di; Chmiel, Anna; Czaplicka, Agnieszka; Dąbrowski, Grzegorz; Garas, Antonios; Garcia, David; Gobron, Stéphane; Hillmann, Robert; Hołyst, Janusz; et al. (Procedia Computer Science)

Dynamische Analyse von Netzwerken elektronischer Kommunikation. Kann der Zentralität getraut werden? - Trier, Matthias; Bobrik, Annette (Netzwerkanalyse und Netzwerktheorie)

Anwendungsszenarien als Werkzeug zur (V)Ermittlung des Nutzens von Corporate Social Software - Richter, Alexander; Mörl, Susanne; Trier, Matthias; Koch, Michael

The Use of Instant Messaging in Working Relationship Development: A Case Study - Cho, Hee-Kyung; Trier, Matthias; Kim, Eunhee (Journal of Computer-Mediated Communication)

Struktur und Dynamik in der Netzwerkanalyse - Trier, Matthias (Handbuch Netzwerkforschung)

Towards a Systematic Approach for Capturing Knowledge-Intensive Business Processes - Trier, Matthias; Müller, Claudia (Practical Aspects of Knowledge Management)

Analyzing the Dynamics of Community Formation Using Brokering Activities - Trier, Matthias; Bobrik, Annette (Communities and Technologies 2007)

Social Search: Exploring and Searching Social Architectures in Digital Networks - Trier, Matthias; Bobrik, Annette (IEEE Internet Computing)

Enabling social media content quality assurance using social network analysis - Sanmateu, Maria-Amparo; Trier, Matthias; Lienicke, Andreas; Rederer, Andreas (9th International Conference On Innovative Internet Community Systems I2CS 2010)

Content-based Community Detection in Social Corpora - Bobrik, Annette; Trier, Matthias (Proceedings Wirtschaftsinformatik)

Odp2cp – ein rapid E-Learning Ansatz zur einfachen Produktion Scorm-konformer Lerninhalte - Trier, Matthias; Herzog, Michael; Möller, Daniel (Proceedings Wirtschaftsinformatik)

Research Note—Towards Dynamic Visualization for Understanding Evolution of Digital Communication Networks - Trier, Matthias (Information Systems Research)

Multimedia Production with a Content HUB Environment. Media Engineering for Mobile Computing Courseware - Herzog, Michael A.; Trier, Matthias (2007 4th IEEE Workshop on Intelligent Data Acquisition and Advanced Computing Systems: Technology and Applications)

SCORM (Shared Content Object Reference Model) - Trier, Matthias (Enzyklopädie der Wirtschaftsinformatik – Online-Lexikon)

Workflow-Modellierung - Krallmann, H.; Trier, Matthias (Enzyklopädie der Wirtschaftsinformatik – Online-Lexikon)

Systemanalyse - Krallmann, H.; Trier, Matthias (Enzyklopädie der Wirtschaftsinformatik – Online-Lexikon)

Virtual Knowledge Communities - IT-supported Visualization and Analysis - Trier, Matthias

Systemanalyse zur Verbesserung von Geschäftsprozessen - Aier, Stephan; Haarlaender, Nico (Systemanalyse im Unternehmen : Prozessorientierte Methoden der Wirtschaftsinformatik)

Generische Transformation von Learning-Content - Das MOCCA-Projekt - Herzog, Michael A.; Trier, Matthias (Proceedings Wirtschaftsinformatik 2007)

Towards Understanding the Dynamics of Digital Communication Networks - Trier, Matthias; Bobrik, Annette; Bartels, Tilmann (Proceedings Wirtschaftsinformatik 2007)

Ein Ansatz zur prozessorientierten Evaluation von Learning Management Systemen - Luther, Michael; Trier, Matthias (Proceedings Wirtschaftsinformatik 2007)

IRIS (1978-2006) Historical Reflection through Visual Analysis - Molka-Danielsen, Judith; Trier, Matthias; Shlyk, Vadim; Bobrik, Annette; Nurminen, Markku I. (Proceedings of IRIS30, Tampere, 2007)
IRIS (Information Systems Research in Scandinavia) Conference is an annual meeting for researchers in Scandinavia. Through 29 annual conference meetings a social network of co-authorships and general research collaboration has emerged. This article contributes a historical reflection and analysis of the social network of researchers associated with the IRIS in the period from 1978 to 2006. We make use of the network visualization and analysis tool called Commetrix. We will examine the influence of certain researchers in this network by identifying their betweenness centrality and degree centrality. We will reflect on the nature and characteristic of the research topics by analyzing the network of keywords found in the conference paper titles, and visualizing their representation in the network.

Content und Kommunikation: Von der Dichotomie zur Kombination - Trier, Matthias (Content Engineering)

Systemanalyse im Wissensmanagement - Trier, Matthias; Bobrik, A. (Systemanalyse im Unternehmen - Prozessorientierte Methoden der Wirtschaftsinformatik)

Systemanalyse - Krallmann, Hermann; Trier, Matthias (Systemanalyse im Unternehmen - Prozessorientierte Methoden der Wirtschaftsinformatik)
Keywords: Prozessorientierung Systemanalyse Wirtschaftsinformatik ITeG_233

Systemtheorie und Modell - Trier, Matthias; Bobrik, A.; Neumann, N.; Wyssussek, B. (Systemanalyse im Unternehmen – Prozessorientierte Methoden in der Wirtschaftsinformatik)

Modellüberblick - Bobrik, A.; Trier, Matthias (Systemanalyse im Unternehmen – Prozessorientierte Methoden in der Wirtschaftsinformatik)

Projektmanagement - Frank, H.; Trier, Matthias (Systemanalyse im Unternehmen – Prozessorientierte Methoden in der Wirtschaftsinformatik)

IT-gestützte Visualisierung und Analyse von virtuellen Kontaktnetzwerken - Anwendungsfelder, Methodik und Vorteile - Bobrik, A.; Trier, Matthias (Analyse sozialer Netzwerke und Social Software - Grundlagen und Anwendungsbeispiele)

Production engineering for video based e- and m-learning content - Herzog, Michael A.; Trier, Matthias; Sieck, Jürgen (Proceedings of UNESCO International Centre for Engineering Education (UICEE) 10th Baltic Seminar on Engineering Education)

Towards a Social Network Intelligence Tool for visual Analysis of Virtual Communication Networks - Trier, Matthias (Virtuelle Organisationen und Neue Medien)

IT-gestützte Modellierung und Analyse elektronischer Expertengemeinschaften (Modeling and Evaluation of Electronic Expert Communities) - Trier, Matthias (i-com)

Process-Oriented Production of Learning Units for Sustainable E-Learning Offerings - Müller, Claudia; Trier, Matthias; Herzog, Michael A. (E-Learning)

A Tool for IT-supported Visualization and Analysis of Virtual Communication Networks in Knowledge Communities - Trier, Matthias (Wirtschaftsinformatik 2005)

A Procedural Model for the Production of Reusable and Standard-Compliant E-Learning Offerings - Müller, Claudia; Trier, Matthias (Wirtschaftsinformatik 2005)

IT-Supported Visualization of Knowledge Community Structures - Trier, Matthias (Proceedings of the 38th Annual Hawaii International Conference on System Sciences)

Netzwerkorientiertes Wissensmanagement und seine Unterstützung durch Softwarewerkzeuge - Krallmann, Hermann; Trier, Matthias (Strategisches Wertschöpfungsmanagement in dynamischer Umwelt: Festschrift für Erich Zahn)

Effiziente Videoproduktionsprozesse fuer komponentenbasierte E-Learning Inhalte - Trier, Matthias; Müller, Claudia; Herzog, Michael (Proceedings Potsdamer Multimedia Konferenz 2004)

Konzepte für die Videoproduktion in virtuellen Lernszenarien Beitrag zum Kollegiatentag 2004 des SVKB - Herzog, Michael A.; Trier, Matthias

IT-Supported Monitoring and Analysis of Social Networks in Virtual Knowledge Communities - Trier, Matthias (Proceedings Sunbelt XXIV Conference, Portoroz, Slovene, INSNA Association, 2004)

Measuring Brokering Activity - a novel measure for dynamic network evolution - Trier, Matthias; Bobrik, A. (Proceedings Sunbelt XXVII Conference, Corfu, Greece, INSNA Association, 2007.)

Einsatzbarrieren fuer Produktkonfiguratoren in der Automatisierungstechnik - Ergebnisse einer empirischen Untersuchung - Szydlowski, M.; Greve-Ecker, I.; Trier, Matthias (Industrie Management Journal 1/2003)

Anforderungen an die IT-Unterstuetzung für Communities of Practice im Unternehmen (in German) - Trier, Matthias (Industrie Management Journal)

Der 'Short-Clip' als Ansatz zur Produktion von video-basiertem E-Learning Content bei der VGU (in German) - Trier, Matthias; Herzog, Michael; Krallmann, Hermann (Proceedings Wirtschaftsinformatik 2003)

Integrating Communities of Practice with e-learning platforms to improve on-the-job-learning - Trier, Matthias (Proceedings of Organizational Knowledge, Learning and Capabilities Conference OKLC 2003, Barcelona, 13. April 2003.)
In knowledge intense business processes, a complex and dynamic body of knowledge is being built bottom-up by experience learning during exception handling and problem solving. Traditional qualification programs do not very effectively provide the special skills required. Communities of Practice are better supporting this dynamic on-the-job learning across hierarchies. Still, CoP approaches and platforms in many organisations can be improved by enriching them with e-learning components to create a connection between the unstructured personalisation strategy of CoPs and the structured training materials. Similarly, e-learning benefits from being linked to communities. In the article, the connections of both areas are analysed to derive a framework for integration. It proposes an agenda of activities for the two domains people-oriented and content-oriented integration of community management and e- learning. These two aspects affect the handling, configuration and design of software features. In a first stage, the challenge is mainly a management and organisational task. Consecutively, the integration processes can be further assessed in order to identify potentials for IT-automatisation.

IT-unterstuetztes Management virtueller Communities of Practice (in German) - Trier, Matthias (Proceedings DoIT Congress 2003, 24.11.2003)

Communities - Management und Unterstuetzung (in German) - Trier, Matthias (Wissensmanagement, Strategien, Prozesse, Communities)

Wissensmanagement - Schoenherr, M.; Trier, Matthias (Systemanalyse im Unternehmen)

IT-Unterstützung im Customer Relationship Management - Trier, Matthias (Industrie Management Journal)